High-resolution inspection of tools for novel forming processes by an endoscopic fringe projection system - Hinz, L.; Schulte, Robert; Kästner, M.; Reithmeier, E. (Optics InfoBase Conference Papers, 2020)
The inspection of tools in sheet-bulk metal forming poses special challenges for metrology. By using a fiber-optic fringe projection system, filigree, internal structures can be measured and the wear can be described by comparison with previous measurements.
CRIS-Team Scopus Importer:2024-12-16